Influence of strategic physical resources on performance of small and medium manufacturing enterprises in Kenya - Muturi Moses Murimi; Beatrice Ombaka; Joseph Muchiri (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This study sought to determine the influence of strategic physical resources on performance of small and medium manufacturing enterprises in Kenya. Anchored on the Resource Based View (RBV) theory the study adopted positivism research philosophy descriptive and causal-effect research designs. Design/methodology/approach: The population for the study comprised of the management staff of the 350 small and medium manufacturing enterprises registered by the Kenya Association of Manufacturers (KAM) where a sample of 183 participants was chosen using stratified sampling method. The study tested for content validity as well as reliability using internal consistency of the questionnaire using Cronbach alpha coefficient. Data analysis was conducted using descriptive statistics and regression analysis to conclude that physical resources have a significant influence on performance of small and medium manufacturing enterprises in Kenya. Findings: Consequently the study recommended that the management of SMEs should ensure that they invest significantly in these resources so as to maximise on the performance of these firms. However the conclusions reached in this paper were based on data collected from small and medium manufacturing enterprises in Kenya. For this reason, the results of the study suffer from generalizability since they may not be inferred on other firms other than manufacturing firms in the sector with similar characteristics. Originality/value: The findings of this study significantly contribute to the existing pool of knowledge regarding the concept of intellectual capital and its implications on organizational performance. Scholars and other researchers would find the outcomes of this study relevant as reference material to advance in their research.
Keywords: L60; M11; M13; 330; Performance; Resources; Strategy; Strategic Physical Resources; Small and Medium Manufacturing Enterprises